Mantenimiento correctivo a banco didáctico de transmisión de potencia mecánica de la Universidad Antonio Nariño sede Cartagena (2023)
This project addresses the issue of corrective maintenance, due to the poor condition and nonoperationality of the mechanical power transmission didactic bench that is located in the laboratory of the Antonio Nariño University, Cartagena. The main objective is to carry out a corrective maintenance plan for the equipment to put it into operation, for this phase to follow are proposed. The theoretical development is based on the review of academic documentation and data collection. With the execution of this project it is diagnosed, faults are corrected and the equipment is restored.